MyPyramid Plan for Daily Food and Calorie Intake - Glenda L. Warren (EDIS)
FCS-8800, a 2-page fact sheet by Glenda Warren, offers two charts showing recommended daily calorie and food group intake for people of different ages and activity levels. Based on the U.S. government's MyPyramid plan. Published by the UF Department of Family, Youth and Community Sciences, December 2007.